Fetomaternal Outcomes of Obstructed Labour in Tertiary Care Hospital Dera Ismail Khan: Fetomaternal Outcomes of Obstructed Labour - Bibi, Najma; Anwar, Sadia; Ghafoor, Maria; Saleem, Umm-e-Aimen; Zaman, Uzma; Latif, Nayar; Malik, Shumaila Noreen (Pakistan Journal of Health Sciences, 2024)
Strong contractions that prevent the fetus from moving through the birth canal, known as obstructed labour, were often due to a mismatch between the size of the fetal head and the pelvis. Despite being preventable, this condition significantly contributes to maternal and neonatal morbidity and mortality and is a leading cause of hospitalization. Objective: To assess the frequency and types of adverse maternal and fetal outcomes associated with obstructed labour in Tertiary Care Hospital, Dera Ismail Khan. Methods: This cross-sectional study was conducted at the Department of Obstetrics and Gynecology, Gomal Medical College, Dera Ismail Khan, from December 1, 2021 to June 1, 2022. The sample size was 193 calculated using WHO sample size software by convenient sampling technique. Adverse fetomaternal outcomes such as bladder trauma, uterine rupture, hysterectomy, sepsis, Postpartum Hemorrhage (PPH), birth asphyxia, and stillbirth were the outcomes of the study. All the data were entered on a pre-designed proforma and analyzed by SPSS version 25.0. Results: The age range for pregnant women was Participants between 18 to 40 years with a mean age of 28.689±3.05 years, the average gestational age was 37.492±2.24 weeks and the average parity was 1.507±1.51. Bladder trauma was observed in 8.3% of patients, ruptured uterus 15.5%, hysterectomy 7.8%, sepsis 19.2%, PPH 6.2%, birth asphyxia 56.5%, and stillbirth was 33.2%. Conclusions: This obstetrical emergency affects relatively younger women with a mean age of 28.69 years, with a mean gestational age of 37.49 weeks. Birth asphyxia and stillbirth were the common outcomes while maternal bladder trauma uterine rupture, hysterectomy sepsis, and postpartum hemorrhage were significant.